Syntrophy drives the microbial electrochemical oxidation of toluene in a continuous-flow "bioelectric well". Issue 3 (June 2022) - Tucci, Matteo; Milani, Alessandro; Resitano, Marco; Viggi, Carolina Cruz; Giampaoli, Ottavia; Miccheli, Alfredo; Crognale, Simona; Matturro, Bruna; Rossetti, Simona; Harnisch, Falk; Aulenta, Federico
Abstract: Microbial electrochemical technologies (MET) are promising for the remediation of groundwater pollutants such as petroleum hydrocarbons (PH). Indeed, MET can provide virtually inexhaustible electron donors or acceptors directly in the subsurface environment. However, the degradation mechanisms linking contaminants removal to electric current flow are still largely unknown, hindering the development of robust design criteria. Here, we analysed the degradation of toluene, a model PH, in a bioelectrochemical reactor known as "bioelectric well" operated in continuous-flow mode at various influent toluene concentrations. With increasing concentration of toluene, the removal rate increased while the current tended to a plateau, hence the columbic efficiency decreased. Operation at open circuit confirmed that the bioelectrochemical degradation of toluene proceeded via a syntrophic pathway involving cooperation between different microbial populations. First of all, hydrocarbon degraders quickly converted toluene into metabolic intermediates probably by breaking the aromatic ring upon fumarate addition. Subsequently, fermentative bacteria converted these intermediates into volatile fatty acids (VFA) and likely also H2, which were then used as substrates by electroactive microorganisms forming the anodic biofilm. As toluene degradation is faster than subsequent conversion steps, the increase in intermediate concentration could not result in a current increase. This work provides valuable insights on the syntrophic degradation of BTEX, which are essential for the application of microbial electrochemical system to groundwater remediation of petroleum hydrocarbons. Graphical Abstract: ga1 Highlights: Bioelectrochemical reactor for toluene bioremediation. Microbial syntrophy involved in toluene conversion into electric current. Syntrophic cooperation between hydrocarbon degraders and electroactive bacteria. VFAs served as metabolic intermediates in microbial cross-feeding.